Exact Solution of the Startup Electroosmotic Flow of Generalized Maxwell Fluids in Triangular Microducts - Siginer, D (American Society of Mechanical Engineers, 2021)
The unsteady electroosmotic flow of generalized Maxwell fluids in triangular microducts is investigated. The governing equation is formulated with Caputo-Fabrizio time-fractional derivatives whose orders are distributed in the interval [0, 1). The linear momentum and the Poisson-Boltzmann equations are solved analytically in tandem in the triangular region with the help of the Helmholtz eigenvalue problem and Laplace transforms. The analytical solution developed is exact. The solution technique used is new, leads to exact solutions, is completely different from those available in the literature, and applies to other similar problems. The new expression for the velocity field displays experimentally observed velocity overshoot as opposed to existing analytical studies none of which can predict the overshoot phenomenon. We show that when Caputo-Fabrizio time-fractional derivatives approach unity the exact solution for the classical upper convected Maxwell fluid is obtained. The presence of elasticity in the constitutive structure alters the Newtonian velocity profiles drastically. The influence of pertinent parameters on the flow field is explored. © 2021 American Society of Mechanical Engineers (ASME). All rights reserved.